STUDY OF SOLAR PHOTOVOLTAIC SYSTEM USING DATA ACQUISITION - N.Janaki (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Renewable energy resources are becoming one of primary sources of energy due to its abundance. Today, as civilization grows rapidly various challenges are occur in front of energy structure. Because of interest regarding pollution and global warming demand of renewable energy resources are increased. Solar energy is most promising source of renewable energy sources because of its abundance, versatility and environmental friendly nature. Evolution and utilization of this energy not only provide way to use of these resources but also produce efficient assessment to adjust resources in better way to overcome energy resource crisis. There are different environmental and geographical factors that affect resources, so measurement of solar resources under these factors make system cost effective and enhance usage rate of renewable solar energy. Data acquisition helps to measure status of solar systems under these factors. Accuracy of data acquisition system is also important because various instruments are used to obtain data from system and may produce different results that cause a serious impact on a large scale solar system. Usually, this data acquisition system uses a controller AT89C51, Analog to Digital converter ADC0831, and various communication modules. Some software modules also used to make data acquisition efficient and flexible.